Entrepreneurship in South Africa : a comparative study between the Global Entrepreneurship Monitor, the Global Entrepreneurship Index and opinions of industry experts in the entrepreneurship field - Marks, Jonathan (University of Pretoria, 2016)
Mini Dissertation (MBA)--University of Pretoria, 2016.